Predictors and evolution of post-stroke depression among adults admitted for first stroke at referral hospitals in Dodoma, Tanzania: A protocol for a prospective longitudinal observational study - Sadiki Mandari; Azan Nyundo (PLoS ONE, 2026)
Background Survivors of strokes are prone to disabilities, especially in underdeveloped countries. Post-stroke depression (PSD) is a common neuropsychiatric condition that exacerbates symptoms and raises the danger of stroke recurrence, disability, and mortality. Nevertheless, little is documented about PSD’s incidence, predictors, and consequences. This study aims to assess predictors and outcomes of post-stroke depression among patients admitted with the first stroke episode at referral hospitals in Dodoma, Tanzania. Methods and analysis The study is a prospective longitudinal observational design; a consecutive sampling technique will be used to attain the estimated sample size of adults aged ≥18 years who have had their first stroke episode, within 14 days. The study will be conducted at referral hospitals in the Dodoma region, Tanzania. At admission, baseline clinical and sociodemographic parameters will be recorded, including relevant medical and psychiatric history. Depressive symptoms will be assessed at 1- and 3-months post-stroke, with the 1-month assessment serving as the baseline for post-stroke depression. The International Neuropsychiatric Interview (M.I.N.I) will be used to diagnose major depressive disorder and to exclude participants with a prior history of depression, while the PHQ-9 will be used to quantify severity and monitor progression of depressive symptoms over time. Data will be summarised using descriptive statistics; continuous data will be reported as mean (SD) or median (IQR), while categorical data will be reported as frequencies and proportions. The PSD predictors will be determined using logistic regression analysis. The study will adhere to data-sharing guidelines and take ethical considerations into account. Ethics and dissemination The University of Dodoma’s institutional Research Review and Ethical Committee has granted permission to conduct the study with reference number MA.84/261/02. The relevant authorities granted approval for the study to be carried out at DRRH and BMH.